THE USE OF TABOO LANGUAGE AS POLITICAL EXPRESSION ON X SOCIAL MEDIA - Nadia Aulia Rahmah; Indah Arvianti; Ahmad Muhid (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
The increasing number of controversial government policies in Indonesia has sparked reactions from the public, especially on social media platforms such as X. Interestingly, high ranking officials, including the president, use taboo words in public. This study aims to identify the types of taboo words used by netizens in their criticism of the government and seek the reasons behind their use, as well as how the public views the use of taboo words in political criticism. Using a qualitative approach, this study analyzed several tweets containing taboo words. The findings show that all six categories of taboo words proposed by Wardhaugh were found in the data, along with additional types, such as insults to intelligence. The use of taboo words is often motivated by strong emotions such as anger and disappointment, and in some cases, by the belief that certain officials deserve harsh criticism. Society's response was divided: some people saw it as a legitimate form of emotional expression and resistance, while others found it inappropriate, although many normalized it. Overall, this study concludes that taboo words serve as a powerful tool for expressing disappointment and anger and suggests that future research could examine similar expressions on other platforms or in different contexts.